2007
DOI: 10.1152/ajpheart.01150.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-6 in cardiac inflammation and dysfunction after burn complicated by sepsis

Abstract: To examine the role of myocardial interleukin-6 (IL-6) in myocardial inflammation and dysfunction after burn complicated by sepsis, we performed 40% total body surface area contact burn followed by late (7 days) Streptococcus pneumoniae pneumonia sepsis in wild-type (WT) mice, IL-6 knockout (IL-6 KO) mice, and transgenic mice overexpressing IL-6 in the myocardium (TG). Twenty-four hours after sepsis was induced, isolated cardiomyocytes were harvested and cultured in vitro, and supernatant concentrations of IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 46 publications
3
46
0
1
Order By: Relevance
“…Consistent with published results (91,93), we found that burn caused significant inflammatory infiltration and disorganization of cardiomyocytes (Fig. 10B).…”
Section: Estradiol Decreases Myocardial Damage and Improves Cardiac Fsupporting
confidence: 93%
“…Consistent with published results (91,93), we found that burn caused significant inflammatory infiltration and disorganization of cardiomyocytes (Fig. 10B).…”
Section: Estradiol Decreases Myocardial Damage and Improves Cardiac Fsupporting
confidence: 93%
“…Various factors contribute to the deteriorated LV function, such as inflammation, free radicals, toxins, and mitochondrial dysfunction [20][21][22][23][24]. Increasing evidence validates the correlation between myocardial dysfunction and high mortality rates [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the results of our study, it showed that, compared with the normal control group and the sham operation group, the serum level of TNF-α in the model group and the sham BP treatment group had significantly increased, while compared with the model group and the sham BP treatment group, the serum level of TNF-α in the BP treatment group had significantly decreased. The uncommon effect they observed with TNF-α could be explained by that the level of TNF-α was negatively correlated with cardiac function in the occurrence of sepsis [26]. As the main anti-inflammatory cytokine, IL-10 functions at immune suppression and plays an anti-inflammatory role [27].…”
Section: Discussionmentioning
confidence: 99%